Comprehensive Insights into the Neutrophil Percentage to Albumin Ratio (NPAR): An Emerging Integrated Biomarker for Inflammation and Prognosis: Neutrophil Percentage to Albumin Ratio: Emerging Integrated Biomarker for Inflammation - Wadood, Maeesa; Memon, Abeer; Salman, Wardah; Iftikhar, Anum; Raza, Fatima; Ahsan, Naveed; Hussain, Muhammad (Pakistan Journal of Health Sciences, 2024)
Neutrophil Percentage to Albumin Ratio is a new biomarker that measures inflammation severity and prognosis in many inflammatory diseases. Objectives: To systematically assess the role of neutrophil percentage to albumin ratio in predicting inflammation and patient prognosis compared to conventional biomarkers C-reactive protein and procalcitonin, in inflammatory diseases. Methods: PRISMA guidelines were followed by electronic databases such as PubMed, Science Direct, and Google Scholar using keywords including ’Neutrophil Percentage to Albumin Ratio’, ’inflammation’, ’biomarkers’ and ’prognoses’ from 2014 to 2024. Some studies examined the interaction between neutrophil percentage to albumin ratio with systemic inflammation, immune dysfunction and organ injury. Two aspects were analysed comprehensively regarding the comparison of neutrophil percentage to albumin ratio with conventional inflammation biomarkers with consideration of age, baseline characteristics, and comorbidity along with the neutrophil percentage to albumin ratio evaluation in the spectrum of various disorders. A total of 99 studies were taken into consideration for initial screening, finally, 18 studies were taken for in-depth analysis. Results: The review showed a significant correlation between higher values of neutrophil percentage to albumin ratio and inflammation, organ, and clinical deterioration. neutrophil percentage to albumin ratio demonstrates higher accuracy in evaluating the severity of inflammation and patient prognosis compared to classical markers, particularly in critical conditions. Conclusions: It was concluded that neutrophil percentage to albumin ratio becomes ideal as a stable multiple biomarker to measure inflammation and the overall patient prognosis. Utilization of markers in clinical practice could lead to improved recognition of severe inflammation states